Tính chủ động và tích cực trong học tập của sinh viên ngành Giáo dục mầm non Trường Đại học Thủ đô Hà Nội: Thực trạng và đề xuất biện pháp - Nguyễn, Thị Vinh; Đặng, Út Phượng (Tạp chí Giáo dục, 2025)
In the context of educational innovation and the requirement to improve the quality of preschool teacher training towards competence development, promoting students' initiative and positivity in learning is becoming increasingly important. The study was conducted at Hanoi Capital University, focusing on students majoring in Preschool Education in the context of educational innovation, when promoting initiative and positivity in learning has become an urgent requirement. The survey results show that many students still study passively, lacking creativity, affecting their future career capacity. The study identified factors such as teaching methods, learning motivation, environment and practical experience that have a clear impact on the level of initiative of learners. Students show higher initiative when participating in experiential learning activities that are interactive and linked to practice. From there, the study proposes a number of measures to enhance self-study spirit and initiative. The research results also suggest a new approach to preschool teacher training in the direction of competence development.